2021
DOI: 10.1536/ihj.20-600
|View full text |Cite
|
Sign up to set email alerts
|

MiR-448-5p/VEGFA Axis Protects Cardiomyocytes from Hypoxia Through Regulating the FAS/FAS-L Signaling Pathway

Abstract: Bioinformatics analysis showed that miR-448-5p expression in the myocardial tissue of rats with myocardial infarction significantly increased, suggesting that it may participate in myocardial cell apoptosis in myocardial infarction. This study aimed to explore the protective effects of miR-448-5p on hypoxic myocardial cells.H9C2 cells were cultured and subjected to anoxia for 2, 4, and 8 hours to establish a hypoxia model. MiR-448-5p mimic and inhibitor were transfected into the cells; then, a dual-luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, miR-15a-5p suppresses the inflammatory response of human peritoneal interstitial cells by targeting VEGFA ( Shang et al, 2018 ). VEGFA promotes cardiomyocyte apoptosis induced by hypoxia, and miR-448-5p targeting VEGFA can inhibit the expression of Caspase3 ( Tang et al, 2021 ). The binding energy of EGCG and VEGFA is 5.45 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-15a-5p suppresses the inflammatory response of human peritoneal interstitial cells by targeting VEGFA ( Shang et al, 2018 ). VEGFA promotes cardiomyocyte apoptosis induced by hypoxia, and miR-448-5p targeting VEGFA can inhibit the expression of Caspase3 ( Tang et al, 2021 ). The binding energy of EGCG and VEGFA is 5.45 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Both vivo and in vitro studies have demonstrated that Fas mAb can bind to Fas, resulting in the death of cells expressing Fas. Thus Fas, as a target, is considered a key factor in cell death (19). High expression of Fas on the cell membrane is thus highly indicative of the susceptibility of Fas signaling pathway to induce apoptosis; however, the cutoff value between tumor cells is not uniform.…”
Section: Discussionmentioning
confidence: 99%
“…For miR-448, no alteration in the brain following stroke was reported, nor a connection to ischemic stroke and blood levels. A study utilizing a spinal cord ischemia/reperfusion injury model reported increased levels of miR-448 measured by qRT-PCR [ 44 ] and in cell hypoxic culture models of myocardial infarction [ 31 , 45 ]. The studies, as mentioned above, on miRNA alteration in ischemic stroke have either been performed in the cerebral cortex, the blood serum, or the researchers did not indicate the exact location.…”
Section: Discussionmentioning
confidence: 99%
“…The last miRNA, miR-448-5p, was also scarcely studied until now. One study found VEGFA (vascular endothelial growth factor A) to be a target and a regulator of the FAS/FAS-L signaling pathway in a hypoxia model in myocardial rat cells [ 31 ]. VEGFA is known for angiogenesis and neuroprotection but seems to have a dual role since it alters vascular permeability and blood–brain barrier integrity in stroke [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%